A systematic revision of the South African Gymnobisiidae (Pseudoscorpiones: Neobisioidea) - Neethling, J.a.; Neethling, C. (Zootaxa, 2023)
The South African fauna of Gymnobisiidae pseudoscorpions is revised. Originally containing only three species in a single genus (Gymnobisium Beier, 1931), results of this study show that there are eight distinct species of the genus within South Africa, five of which are new to science, namely G. capense sp. nov., G. cuneatum sp. nov., G. hogsbackense sp. nov., G. megalodontum sp. nov. and G. prionotogladiatum sp. nov. Three of these, namely G. cuneatum sp. nov., G. hogsbackense sp. nov., and G. inukshuk Harvey and Giribet, 2016 (which is a rare troglobite), are short-range endemics and threatened by habitat loss. Most of the other species, with the exception of G. quadrispinosum (Tullgren, 1907), have small distribution ranges. They are predominantly found inhabiting moist leaf litter of indigenous forests along the coastal provinces, indicating either a low dispersal ability or high niche specificity in these pseudoscorpions. The lack of dense, shaded vegetation between isolated forest patches seems to act as a dispersal barrier for many of the species.